(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Preeclampsia, a hypertensive disorder in pregnancy, affects 2%-8% of pregnancy complications worldwide. Severe internal vasospasm causes renal changes, leading to hypo calcemia and proteinuria. Early diagnosis involves urinary calcium/creatinine levels. Aim of the Study: To evaluate Urinary Calcium/Creatinine ratio in pregnant women with preeclampsia and to check itʼs association with severity of the disease. Patients and Methods: This prospective case-control study was carried out on pregnant women admitted to labor room at Duhok Hospital for Obstetrics and Gynecology from 1st of March to 1st of September 2023, 150 pregnant women participated in this study at third trimester of pregnancy were consecutively divided into 3 groups: a group of women with preeclampsia, women with pregnancy-induced hypertension, and a control group of normotensive pregnant women, and 50 pregnant women for each groups. The calcium/creatinine ratio was estimated and the statistical analysis was done. Results: There was a significant statistical difference among the studied groups regarding the mean maternal age; as it was significantly higher in pregnancy-induced hypertension group than the other two groups (P=0.001). The urinary calcium/creatinine ratio was significantly lower among the preeclampsia (P=0.019) than the control group only. Conclusions: The urinary calcium/creatinine ratio showed lower mean levels in preeclampsia groups compared to control, suggesting it may predict preeclampsia but not detect its severity.